2008
DOI: 10.1002/em.20395
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic damage in female Pakistani agricultural workers exposed to pesticides

Abstract: Bhawalpur is a major cotton-growing area in Pakistan. Cotton picking in Pakistan is carried out by females and as a result of the intensive use of pesticides during the growing season these females are exposed to pesticide residues in the picking season. In the present study, peripheral blood was obtained from 69 cotton pickers and 69 unexposed females and used to assess the effect of pesticide exposure on genetic damage as well as on hepatic enzymes and serum cholinesterase. The subjects were of similar avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…The decrease in plasma albumin and in the total plasma protein indicated hepatocellular dysfunction or liver disease (Kumar et al, 2005). Elevated levels of ALT and AST observed in this study (Table VII) may be due to pathological changes such as necrosis of hepatocytes, which caused an increase in the permeability of the cell membranes, resulting in the release of aminotransferases into the blood stream (Ali et al, 2008). ALT has been reported to be a marker with a high specificity for acute hepatocellular injury (Friedman et al, 1996).…”
Section: Discussionmentioning
confidence: 71%
“…The decrease in plasma albumin and in the total plasma protein indicated hepatocellular dysfunction or liver disease (Kumar et al, 2005). Elevated levels of ALT and AST observed in this study (Table VII) may be due to pathological changes such as necrosis of hepatocytes, which caused an increase in the permeability of the cell membranes, resulting in the release of aminotransferases into the blood stream (Ali et al, 2008). ALT has been reported to be a marker with a high specificity for acute hepatocellular injury (Friedman et al, 1996).…”
Section: Discussionmentioning
confidence: 71%
“…Organochlorine pesticides have well documented estrogenic effects [18,19]. Another case-control study has demonstrated an increase in cytogenetic damage that correlates with increasing age in women with occupational exposure to pesticides [20]. An alternative explanation is the potential for more frequent use of assisted reproductive technologies in older women.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, polymorphisms in metabolism and DNA-repair genes may modulate the extent of DNA damage in pesticide-exposed workers [33]. Since the AFs are frequently exposed to mixture of pesticides, it is diffi cult to attribute the genotoxic damage [31,36,37]. A progressive increase in spontaneous chromosome instability/chromosomal loss due to the aging process is associated with the accumulation of DNA damage which is caused by age-related decline in DNA repair capacity [38].…”
Section: Discussionmentioning
confidence: 99%